2019
DOI: 10.1016/j.ihj.2019.12.004
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and angiographic profile of very young adults presenting with first acute myocardial infarction: Data from a tertiary care center in Central India

Abstract: Acute myocardial infarction (AMI) is afflicting young individuals more frequently nowadays. The present study was planned to evaluate the clinical and angiographic profile in adults aged less than 30 years, presenting with first AMI as data from Central India is very scarce. This cross-sectional study included 41 patients of STEMI with a mean age of 27 ± 2.8 years. Risk factors were male gender (95.1%), dyslipidemia (51.2%), tobacco consumption (48.8%), obesity (34.1%), and smoking (29.3%). Anterior wall myoca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
25
0
9

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(36 citation statements)
references
References 12 publications
2
25
0
9
Order By: Relevance
“…[ 20 ] Hence, young adults with dyslipidaemia are more prone to develop CVDs. [ 21 ] A higher incidence rate (87.1%) of patients with one or multiple comorbidities in the present study suggest the high prevalence of diabetes and/or hypertension among patients with dyslipidaemia. Altogether these comorbidities may contribute to the increased risk of atherosclerotic CVDs.…”
Section: Discussionmentioning
confidence: 53%
“…[ 20 ] Hence, young adults with dyslipidaemia are more prone to develop CVDs. [ 21 ] A higher incidence rate (87.1%) of patients with one or multiple comorbidities in the present study suggest the high prevalence of diabetes and/or hypertension among patients with dyslipidaemia. Altogether these comorbidities may contribute to the increased risk of atherosclerotic CVDs.…”
Section: Discussionmentioning
confidence: 53%
“…Another cross-sectional study evaluated 41 STEMI patients and revealed that anterior wall MI was found in 82.9%, with obstructive CAD in 61% of patients due to involvement of LAD in 46.4% ( 10 ).…”
Section: Discussionmentioning
confidence: 99%
“…Dyslipidemia was defined as serum total cholesterol (TC) ≥200 mg/dL, triglyceride (TG) >150 mg/dL, low-density lipoprotein (LDL) > 130 mg/dL, high-density lipoprotein (HDL) <50 mg/dL in women and <40 mg/dL in men, and/or those being treated with lipid-lowering therapy. 12 As thrombus load was concerned, if the largest diameter of thrombosis was twice larger than the vessel’s one, it was defined as large thrombosis, otherwise small thrombosis. 13 , 14 Reinfarction was defined as recurrence of ≥0.1 mV ST-segment elevation in at least two contiguous leads, or newly development of pathological Q waves in ECG; and rise of cardiac troponin (cTn) values with at least one value ≥20% of previous one, and the presence of symptoms suggestive of ischemia lasting 20 minutes or more.…”
Section: Methodsmentioning
confidence: 99%
“… 9 Stroke was defined as a focal neurological deficit lasting more than 24 hours due to an ischemic or hemorrhagic event, or a neurological event causing death. 12 Major bleeding was defined as intracranial hemorrhage, cardiac tamponade, hemoglobin value falling more than 5 g/dL even if the bleeding focus could not be determined, and bleeding-related death. Any bleeding was defined by the TIMI criterion.…”
Section: Methodsmentioning
confidence: 99%